2022
DOI: 10.3389/fchem.2022.911232
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzylidene Analogs of Oleanolic Acid as Potential α-Glucosidase and α-Amylase Inhibitors

Abstract: A series of benzylidene analogs of oleanolic acid 4a∼4s were synthesized and assessed for their α-glucosidase and α-amylase inhibitory activities. The results presented that all synthesized analogs exhibited excellent-to-moderate inhibitory effects on α-glucosidase and α-amylase. Analog 4i showed the highest α-glucosidase inhibition (IC50: 0.40 μM), and analog 4o presented the strongest α-amylase inhibition (IC50: 9.59 μM). Inhibition kinetics results showed that analogs 4i and 4o were reversible and mixed-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Among the various classes of compounds obtained from natural resources, triterpenoids also show potent antidiabetic activity, including α-glucosidaseinhibiting effects [8][9][10][11]. For example, oleanolic acid (OA) derivatives, such as oxime esters, showed inhibitory activities against α-glucosidase and α-amylase [12], a series of benzylidene derivatives exhibited excellent to moderate inhibitory effects, and inhibition kinetics results showed that the leading analogs were reversible and mixed-type inhibitors of α-glucosidase and α-amylase [13,14]. OA indole derivatives with various electronwithdrawing groups possessed anti-α-glucosidase activities and demonstrated the capacity to form ligand-enzyme complexes with α-glucosidase enzymes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various classes of compounds obtained from natural resources, triterpenoids also show potent antidiabetic activity, including α-glucosidaseinhibiting effects [8][9][10][11]. For example, oleanolic acid (OA) derivatives, such as oxime esters, showed inhibitory activities against α-glucosidase and α-amylase [12], a series of benzylidene derivatives exhibited excellent to moderate inhibitory effects, and inhibition kinetics results showed that the leading analogs were reversible and mixed-type inhibitors of α-glucosidase and α-amylase [13,14]. OA indole derivatives with various electronwithdrawing groups possessed anti-α-glucosidase activities and demonstrated the capacity to form ligand-enzyme complexes with α-glucosidase enzymes [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, OA had been reported to have α‐glucosidase inhibitory activity [23] . Recently, OA was also taken as a parent compound to be modified structurally as its benzylidene, oxime ester, or indole derivatives, which resulted in the generation of other more potent α‐glucosidase inhibitors [24–26] . Besides, the pyrazole group is also discovered to be one key pharmacophore frequently fused a variety of bioactive compounds represented by the marketed drug sildenafil, [27] and some pyrazole‐fused qunazolinone, benzofuran, pyran were reported to exhibit inhibitory activity against α‐glucosidase [28–30] …”
Section: Introductionmentioning
confidence: 99%